Museums in the digital age changing meanings of place, community, and culture - Bautista, Susana Smith 1966- (Lanham, Maryland AltaMira Press, 2014)
Museums in the Museums in the Digital Age: Changing Meanings of Place, Community, and Culture first provides a theoretical framework of how the critical notions of place, community, and culture are changing in the digital age, respective to the field of museology.
The new museology -- Framing a changing museology in the digital age -- Indianapolis Museum of Art -- Walker Art Center -- San Francisco Museum of Modern Art -- Museum of Modern Art -- Brooklyn Museum -- Greater than five : the Los Angeles county Museum of Art -- A balancing act.
Includes bibliographical references (pages 243-274) and index.
Keywords: Museums -- History -- 21st century; Museums and community; Museums -- Data processing; Museums -- United States -- History -- 21st century; Museums and community -- United States; Museums -- United States -- Data processing; Museums -- United States -- Case studies; Museums -- History -- 21st century; Museums and community; Museums -- Data processing; Museums -- United States -- History -- 21st century; Museums and community -- United States; Museums -- United States -- Data processing; Museums -- United States -- Case studies